Research Methods Pedagogy: Engaging Psychology Students in Research Methods and Statistics - Lynne D. Roberts (Frontiers Research Topics, 2016)
Research methods and statistics are central to the development of professional competence and evidence based psychological practice. Furthermore, the ability to interpret and apply research findings contributes to the development of psychological literacy, the primary outcome of an undergraduate education in psychology. Despite this, many psychology students express little interest in, and in some cases an active dislike of, learning research methods and statistics. This ebook brings together current research, innovative evidence-based practice and critical discourse related to engaging psychology students in learning quantitative and qualitative mixed methods research.